Increased TSPO alleviates neuropathic pain by preventing pyroptosis via the AMPK-PGC-1α pathway - Baolong Li; Kaiming Yu; Xiongyao Zhou; Jialu Sun; Le Qi; Weiye Li; Tuo Yang; Weizhen Li; Ningning Wang; Xiaosong Gu; Shusen Cui; Rangjuan Cao (The Journal of Headache and Pain)
Abstract Neuropathic pain poses a significant clinical challenge, largely due to the incomplete understanding of its molecular mechanisms, particularly the role of mitochondrial dysfunction. Bioinformatics analysis revealed that pyroptosis and inflammatory responses induced by spared nerve injury (SNI) in the spinal dorsal horn play a critical role in the initiation and persistence of neuropathic pain. Among the factors involved, TSPO (translocator protein) emerged as a key regulator. Our experimental findings showed that TSPO expression was upregulated during neuropathic pain, accompanied by mitochondrial dysfunction, specifically manifested as impaired mitochondrial biogenesis, disrupted mitochondrial dynamics (including insufficient expression of mitochondrial biogenesis and fusion-related proteins, as well as significantly increased expression of fission-related proteins), and activation of pyroptosis. Pharmacological upregulation of TSPO, but not its downregulation, effectively alleviated SNI-induced pain hypersensitivity, improving mitochondrial function and reducing pyroptosis. Immunofluorescence staining confirmed that TSPO was primarily localized in astrocytes, and its expression mirrored the protective effects on mitochondrial health and pyroptosis prevention. PCR array analysis suggested a strong association between TSPO and the mitochondrial regulation pathway AMPK-PGC-1α. Notably, inhibition of AMPK-PGC-1α abolished TSPO effects on mitochondrial balance and pyroptosis suppression. Furthermore, Mendelian randomization analysis of GWAS data indicated that increased TSPO expression was linked to pain relief. Through drug screening, molecular docking, and behavioral assays, we identified zopiclone as a promising TSPO-targeting drug for pain treatment. In summary, this study enhances our understanding of the molecular interplay between TSPO, mitochondrial health, and neuropathic pain, highlighting TSPO as a potential therapeutic target for pain management. Graphical Abstract